Wound Complications: Subcuticular Suture versus Skin Staples for Skin Closure after Caesarean Section (Medical Forum Monthly, 2020)
Objective: To compare the frequency of wound infection with subcuticular suture versus skin staples for skin closure after caesarean section.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecology, Jinnah Hospital, Lahore from January 2014 to July 2014.Materials and Methods: A total of 500 cases (250 cases in each group). Patients were randomly divided in two equal groups. Patients in Group A were stitched by subcuticular suture maternal while patients in group B were stitched with metal staples.Results: In group A, mean gestational age was 38.60±1.23 weeks and in group B, 38.71±1.33 weeks. Regarding parity, 120 patients (48.0%) from group A and 127 patients (50.8%) from group B were having parity 0-2. In group A, 130 patients (52.0%) and in group B, 123 patients (49.2%) were para 3-5. Wound infection was observed in 18 patients (7.2%) and 36 patients (14.4%) in groups A and B, respectively. There was a statistically significant difference between two groups (p=0.009).Conclusion: A significantly less wound infection with subcuticular suture when the cesarean delivery skin incision was closed with suture rather than with staples.